A Low Complexity System for Multiple Data Embedding Into H.264 Coded Video Bit-Stream - Ghasempour, Mohammad; Ghanbari, Mohammad (IEEE transactions on circuits and systems for video technology, 2020)
This article investigates the relative performance of multiple data embedding into H.264 compressed video under two schemes of closed-loop and open-loop methods. In closed-loop, a part of an encoder is modified to embed data within the encoding loop during re-compression, while in the open-loop scenario, a part of decoder is modified to embed data out of decoding loop. It is shown, while for the first instance of embedding, both methods behave almost similarly for all picture types, for later instances of embedding, open-loop outperforms the closed-loop method. Moreover, the required time for embedding and extracting processes of open-loop method is only 1-1.5% of that of the closed-loop counterpart. In both methods, the quality of watermarked video and the data hiding capacity are controlled by the position of last non-zero (LNZ) coefficient in the H.264 zigzag scanning order. However, for B-pictures, the side-effect of embedding distortion is very limited (in the order of 0.002 in terms of SSIM), but for I- and P-pictures it can be significant. Picture degradations in I- and P-frames are alleviated by confining data embedding only into the last block of macroblocks of I-frames and the last P-frame in the GOP, respectively. Finally, it is shown that while with CAVLC type entropy coder, the number of increased bits due to data embedding can vary from 5%-65% of the metadata volume (depending on quality degradation) this value with CABAC coder is only less than 20% of that under CAVLC.